DEGRADTION OF DIISOPROPANOLAMINE BY USING FENTON'S OXIDATION - MEGAT KHAMARUDDIN, PUTRI NADZRUL FAIZURA (2012)
Amines are used in the natural gas processing industries to remove acid gases such as carbon dioxide and hydrogen sulphide through the absorption process. Diisopropanolamine (DIPA) is one of the preferred amines for the removal of high concentration of carbon dioxide in natural gas. Absorption process units are prone to corrosion and need to undergo scheduled maintenance activity. This generates wastewater contaminated with DIPA with enhanced chemical oxygen demand (COD). In order to meet the stringent environmental regulatory limits, the wastewater must be treated prior to disposal. Studies have shown that DIPA is not readily degradable. Fenton's oxidation is one technique that is capable of degrading recalcitrant pollutants under mild conditions. This research work reports the investigations on the application of Fenton's oxidation as a new approach to degrade DIPA. The objectives ofthe present research work include testing of the efficacy of Fenton's oxidation to degrade DIPA, identification of the optimum reagents' dosages, reaction pH and temperature and to develop a kinetic model for the degradation of DIPA. All the experiments were conducted in batch mode using synthetically prepared wastewater. The results obtained show that Fenton's oxidation can be applied to degrade DIPA contaminated wastewater successfully. Response Surface Methodology (RSM) was used to ascertain the workable range of reagents' dosages. Within these ranges, the optimum pH was identified as 2.5 using One Factor at a Time (OFAT) approach. Complete degradation of DIPA was found at several combinations of reagents dosages at the temperature of 30°C. DIPA concentration affects the rate of reaction the most, followed by concentration of hydrogen peroxide and then of ferrous ion. The apparent order of reaction determined by using integral method was found to be a second-order with respect to DIPA. This indicates that the reaction is non-elementary in nature. The apparent Arrhenius activation energy is obtained as 122 kJ/mol. A mechanism based reaction kinetic equation was developed and validated with the experimental observations. Optimum dosage ratios of reagents for total degradation of DIPA were identified as H202:DIPA of 23 and H202:Fe2+ of 77.